'The devil is in the level': understanding inequality in Australia's Film, TV and Radio industries. (August 2020) - Luckman, Susan; Anderson, Heather; Sinha, Ruchi; Rentschler, Ruth; Chalklen, Charlotte
This article applies a quantitative analysis of gender diversity variables to custom data sets of 2011 and 2016 Australian Bureau of Statistics Census data for Film, TV and Radio employment. Prima facie, employment figures across a whole sector or employment segment can appear to be broadly representative of the Australian population, but looking more closely, it becomes apparent that the 'devil is in the level'. Although there is often parity at the macro level, drilling down into specific roles and their differential levels of seniority and power reveals inequalities between those in key and more secure gatekeeping positions and those further down the organisational hierarchy. Focusing on gender, this article will argue that the lack of diversity at senior levels of employment is a key contributing factor to lack of diversity within cultural and creative industries, reinforcing power imbalances and social and economic inequity.